Imapct of Service Quality and Pricing on Customer Satisfaction and Loyalty in the Real Estate Industry in Croatia - Vrbanec Dedeić, Danijela; Benazić, Dragan; Ružić, Erik (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Purchasing real estate is one of life’s major decisions due to the size of the investment and the complexity of the process. Rapid changes in the real estate market, including fluctuations in prices and property quality, as well as varying performance among agencies and agents, further complicate the process. The quality of service provided by real estate agencies and their agents plays a crucial role in meeting customer expectations, ensuring satisfaction, and building loyalty. High-quality service fosters trust, reduces transactional risks and costs, and enhances the agency’s business success. This study examines the impact of service quality and pricing on customer satisfaction and loyalty in Croatia through an empirical survey analyzed with PLS methodology. Findings show that service quality significantly affects satisfaction and loyalty, while agency fees have a minor effect. Agencies should invest in professional agents who build trust and provide high-quality information, forming a foundation for long-term relationships.